Laparoscopy findings in infertility patients. Experience at Cayetano Heredia National Hospital. 1995 – 1998 - Franco, Alberto (2015)
OBJECTIVE: Discover the laparoscopic findings in the study of infertility patients. DESIGN: Retrospective descriptive study based on a review of medical records, laparoscopy sheets and sheets infertility patients undergoing diagnostic laparoscopy. MATERIALS AND METHODS: Between January 1995 and December 1998, at the National Hospital Cayetano Heredia diagnostic laparoscopy to 106 infertility patients was performed. The study variables were: Features of infertility (type and time inferlilidad), affiliation, background, symptoms, gynecologic, laparoscopic examination (findings and complications). RESULTS: The secondary infertility was 60.4% and 39.6% Primary; 95.3% showed abnormal laparoscopy; factors were most frequently altered tubal factor (67%) and peritoneal factor (66%). The most frequent pathologies were endometriosis and tubal obstruction (43.4% each). CONCLUSION: Laparoscopy is a safe and useful for the study of infertility method.